THE INFLUENCE OF TEACHER TEACHING METHODS AND LEARNING MOTIVATION ON THE LEARNING OUTCOMES OF IPS SUBJECTS OF SENIOR HIGH SCHOOL MAMBAUS SHOLIHIN STUDENTS SUCI MANYAR GRESIK - Mahfudz Sulaiman; Nurul Huda (Madani : Journal of Social Sciences and Social Science Education, 2024)
In general, this study aims to determine the effect of teaching methods teachers and motivation to learn the results of learning subjects IPS MA students. Mambaus Shoihin Suci Manyar Gresik. Specifically the purpose of this study are (1) Describe the influence of teaching methods teachers to the results of learning subjects IPS Senior High School students. Mambaus Shoihin Suci Manyar Gresik. (2) Describe the influence of learning motivation on learning outcomes ips subjects students MA. Mambaus Shoihin Suci Manyar Gresik. (3) Describe the influence of together teaching methods of teachers and learning motivation on the learning outcomes subjects IPS students MA. Mambaus Sholihin Suci Manyar Gresik.             The population in this study were Senior High School students. Mambaus Shoihin Suci Manyar Gresik academic year 2016/2017 which then taken a sample of 33 students. The data of research about teaching method of teacher and learning motivation is obtained through questionnaire method by using likert scale and student learning result data on IPS subjects obtained from semester 1. Next data is analyzed by using multiple regression technique with computer assistance program of SPSS For Windows version 11.5.           From multiple linear regression analysis test "F test" and "t test" in table correlations. Obtained that the influence of teaching methods teachers is 0.672 which means there is a high enough influence from the teaching methods of teachers to the results of learning subjects Social Studies thus hypothesis 1 received significantly. From the correlations table obtained that the effect of learning motivation on learning outcomes is 0.799 which means there is a high influence between learning motivation and learning outcomes, thus hypothesis 2 received significantly. From the t test model obtained the influence between the teaching methods of teachers and learning motivation by the same to the results of the blajar is 0.732 which means there is a significant influence between the influence of teaching methods of teachers and learning motivation on the results of learning subjects IPS.            Based on the anova then sig = 0.000 (A) which <o.05, from the analysis of coefficient dibermenated by 49.4% and the remaining 50.6% influenced by other factors. So in conclusion there is influence of teaching methods of teachers and motivation to learn the results Learning in addition to the influence of teaching methods, learning motivation seen from the results of the F test then the price significant 0.001 (A) states that the influence of teaching methods, learning motivation to IPS learning results are very convincing thus hypothesis 3 is received significantly.          Based on the results of hypothesis testing obtained conclusion that there is a significant relationship and have a positive correlation direction between the influence of teaching methods teachers and student learning outcomes.ada significant relationship and have a positive correlation direction between the motivation of learning with learning outcomes.secara there is a relationship that Significant and have a positive correlation direction between the influence of teaching methods and learning motivation with student learning outcomes.           For the sake of perfection of the results of this study, then follow-up research to be conducted by other researchers is expected. In the form of research development of other variable variables or in the form of deepening and sharpening research on concrete things. So the results of this study becomes more useful in improving Quality IPS students MA Mambaus Sholihin suci Manyar Gresik.